Future Fiscal and Budgetary Shocks - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2004)
We study here the effects of future tax and budgetary shocks on present levels of economic activity and real interest rates in a nonmonetary and possibly non-Ricardian economy. The paper first takes up an (unanticipated) temporary tax cut to be effective on a given future date—a delayed debt bomb. The sudden prospect of this future-dated shock causes at once a drop in the (unit) value placed on the firms’ business asset, the customer, and accordingly on the price of shares—with the result that the hourly wage, hours worked and GDP drop in tandem. This paradox of reduced activity through announcement of future stimulus does not hinge on an upward jump of long rates of interest, which may or may not occur: the short rate of return on shares is increased by the initial drop in their price, but the price has so much farther to fall that this is more than offset for a time by the expectation of ongoing capital loss, so short rates of interest actually drop. The paper next studies a future tax cut lacking a sunset provision and requiring instead a gradual welfare benefit adjustment to retain solvency. The same negative effects on present activity result. Third, the paper shows that if the tax cut is effective immediately, its effect is ambiguous, as the Marshallian supply-sider effect works the other way. Finally, the paper also examines the new anticipation of a future increase in the number of retirees in a payas- you-go social security program. In conclusion, juxtaposing these results against recent US experience, we hypothesize that the legislation of an unsustainable fiscal gap—the cuts in tax rates and the rise of future obligations owing to the cumulative deficit and the approaching bulge in retirement benefits—is an important cause of the decline in hours worked per employee and in the participation rates over the period